Identifying Influencing Factors of Road Accidents in Emerging Road Accident Blackspots - K. Athiappan; C. Karthik; M. Rajalaskshmi; Chowdhury Subrata; Hamidreza Rabiei Dastjerdi; Yang Liu; Christian Fernández-Campusano; Mehdi Gheisari (Advances in Civil Engineering)
This study deals with identifying the accident blackspots and the influencing factors causing accidents using factored analysis in a medium-sized city (Tirunelveli) in India. From the literature review, the geospatial technique to identify the blackspots and the factors causing accidents was used for analysis. The most influencing factors driving the accidents were identified and ranked based on the repetitive occurrence of accidents in the blackspot area. The spearman ranking system showed the correlation among the factors causing accidents. The factor analysis technique was utilized to identify the key factors driving the repetitive accidents and group them. This study will help transportation planners understand the factors causing accidents and take appropriate measures to reduce the casualties in the road construction planning stage and existing conditions.